Práticas pedagógicas de alfabetização na escola São Miguel II em uma turma multisseriada de 3° ao 5° ano no município de Abaetetuba – Pará - ABREU, Maria de Lourdes Rodrigues de (2024)
This monograph is the result of a study carried out on pedagogical practices of literacy in the school in a multi - series classroom of 3 to 5 years in the city of Abaetetuba - Pará. The study had as participants a teacher and six students. They are inserted in the 3rd and 5th year of elementary school, of the São Miguel II school, which is located on the Douro Joao Miranda Highway km 05 Abaetezinho branch, in the municipality of Abaetetuba-Pa. This study aims to reflect on the pedagogical practices developed by a teacher in a multi-series classroom and the main obstacles faced by him to work. The central question of the research was what are the main obstacles found in the literacy of the multiseriate class in the São Miguel II school? The present research was carried out through a bibliographic study, with theoretical research, in books, articles and on the internet. Possessing a qualitative approach, through field research of the ethnographic type, through the methods of systematic observation and semi-structured interview, using qualitative and quantitative techniques.